1995
DOI: 10.2337/diab.44.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Secretagogues, But Not Glucose, Stimulate an Increase in [Ca2+]i in the Fetal Rat β-cell

Abstract: Fetal pancreatic islets release insulin poorly in response to glucose; however, the cellular mechanism for this is controversial. By using fura 2 to measure changes in the cytoplasmic free Ca2+ concentration ([Ca2+]i) in beta-cells, we have examined islets from fetal, neonatal, and adult rats to determine the ability of glucose and other secretagogues to cause an increase in [Ca2+]i. The effects of glucose (20 mmol/l), glyceraldehyde (20 mmol/l), leucine (20 mmol/l), arginine (20 mmol/l), and the channel effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
4
16
0
Order By: Relevance
“…In addition, the current study has confirmed previous data showing that glucose was unable significantly to stimulate release of insulin from control fetal islets (Weinhaus et al 1995, Tu & Tuch 1996. A possible explanation for this immaturity of function is an insufficient glucose oxidative phosphorylation in mitochondria with inadequate synthesis of ATP (Hughes 1994) and a failure to close ATP-dependent K + channels (Rorsman et al 1989).…”
Section: Tablesupporting
confidence: 79%
“…In addition, the current study has confirmed previous data showing that glucose was unable significantly to stimulate release of insulin from control fetal islets (Weinhaus et al 1995, Tu & Tuch 1996. A possible explanation for this immaturity of function is an insufficient glucose oxidative phosphorylation in mitochondria with inadequate synthesis of ATP (Hughes 1994) and a failure to close ATP-dependent K + channels (Rorsman et al 1989).…”
Section: Tablesupporting
confidence: 79%
“…Arginine is known to stimulate insulin secretion by the mechanisms that are different from those used by glucose, although the detail remains controversial (50,51). However, it seems certain that arginine somehow evoked Ca 2ϩ influx into the ␤ cell, and that leads to the exocytosis of insulincontaining vesicles (52,53). So at least, the decreased insulin secretion in RIP-G Tg might not be due to disorders in exocytosis process.…”
Section: Discussionmentioning
confidence: 99%
“…1 The abbreviations used are: GK, glucokinase; NIDDM, non-insulindependent diabetes mellitus; ES cell, embryonic stem cell; HK, hexokinase; Hanks'-BSA buffer, Hanks'-buffered saline containing 0.2% bovine serum albumin. ments of intracellular calcium concentration were carried out using fura-2 acetoxymethylester (Molecular Probes) (19,20) by the method of Weinhaus et al (20).…”
Section: Methodsmentioning
confidence: 99%
“…A rise in the intracellular Ca 2ϩ concentration in the ␤-cell ([Ca 2ϩ ] i ) is a key event in glucose-stimulated insulin secretion (19,20). Although all the GK-deficient islets looked alike under microscopy, they could be subdivided into two groups in terms of basal [Ca 2ϩ ] i levels; those with normal calcium levels (110 Ϯ 34 nM, n ϭ 7; about 20% of the islets), and those with higher basal calcium levels (higher than 200 nM; about 80%) which might reflect some damage of the islets.…”
Section: Diabetes Mellitus In Mice Lacking ␤-Cell Glucokinase 30254mentioning
confidence: 99%